MANAGEMENT OF HSV-1 AND HSV-2 PRIMARY INFECTION IN ADULT PATIENT: A CASE REPORT - Bima Ewando Kaban; Dahlia Riyanto; Adiastuti Parmadiati; Desiana Radithia; Bagus Soebadi (FKG Unlam, 2021)
ABSTRACT Infection of Herpes Simplex Virus (HSV) type 1 and 2 causes medical problems throughout the world. HSV-1 infection often affects the oral regions and HSV-2 infection is the most prevalent cause of genital ulcerations. It is possible for HSV-2 to cause oro-labial herpes and HSV-1 to cause genital herpes. Primary HSV infection usually affects children or adolescent, whereas adults usually experience infection more frequently due to viral reactivation. Objective: To discuss the management of Primary HSV-1 and HSV-2 Infection which appears simultaneously in adults. Case report: a 33yearold female patient came to hospital with multiple painful ulcers in her tongue, buccal and labial mucosa, preceded by prodrome, followed with eruption and outbreak of vesicles on her skin. The first laboratory examination confirmed a high titer of reactive Immunoglobulin M (IgM) of anti-HSV-1 and Immunoglobulin M (IgM) anti-HSV-2. She was diagnosed to have Primary HSV-1 and HSV-2 Infection and treated with oral Acyclovir and Chlorine dioxide mouthwash with good healing. The clinical presentation, differential diagnosis and management of primary herpetic stomatitis are discussed. Conclusion: Correct diagnosis and treatment can restore well-being, avoid secondary problems for patients, and prevent the use of inappropriate drugs.Keywords : Herpes Simplex Virus, HSV-1, HSV-2, Management, Primary Herpes Infection